Floristics of mangrove tree species in Angke-Kapuk Protected Forest - ONRIZAL ONRIZAL; RUGAYAH RUGAYAH; SUHARDJONO SUHARDJONO (Society for Indonesian Biodiversity, 2005)
Angke-Kapuk Protected Forest with total area 44.76 ha is part of the Tegal Alur-Angke Kapuk mangrove forests. Therefore, this forest has important role as an interface between terrestrial and marine ecosystems, whether physical, biological or social-economic aspects, to determine mangrove ecosystem as a productive and unique ecosystem in the coastal area. However, the study of floristic of the mangrove vegetation in this forest has never to be done previously. According to the study on September to November 2003, in this forest found 8 species of mangrove trees. The tree species can be classified into two groups. The first group is true mangroves (7 species), i.e. Avicennia officinalis, Rhizophora apiculata, R. mucronata, R. stylosa, Sonneratia caseolaris (major component), Excoecaria agallocha, and Xylocarpus moluccensis (minor component). The last group is mangrove associate, i.e. Terminalia catappa. In this forest also found 7 tree species, i.e. Bruguiera gymnorrhiza, Calophyllum inophyllum, Cerbera manghas, Paraserianthes falcataria, Tamarindus indicus, Acacia mangium, and A. auriculiformis as introduced species. The growth level of B. gymnorhiza, C. inophyllum and C. manghas up to now is seedling and sapling, while the growth level of another introduced species is till in pole and tree.